Hubungan Pemenuhan Kebutuhan Biologis Dan Sosial Dengan Tingkat Kecemasan Pada Pasien Hemodialisis Di RSUD Cibinong Tahun 2023 - Kadek Dwi Astuti; Eka Rokhmiati Wahyu Purnamasari; Danur Jaya (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
Kidney failure is a chronic disease where the kidneys are no longer able to remove toxic substances in the body, resulting in a buildup of toxins as a result. Patients suffering from kidney failure must undergo therapy to remove toxic substances, one of the therapies is hemodialysis. This therapy is carried out in approximately 4-5 hours to remove toxins, there are several accesses, namely with CDL and Cimino. which will cause changes in the physical, socio-economic and psychological conditions of patients undergoing Hemodialysis therapy. These changes will have an impact on the patient's coping mechanisms. Patients undergoing hemodialysis often experience several problems including psychological problems, one of which is often experienced is anxiety. Anxiety is an emotional response to a subjective individual assessment, related to feelings of uncertainty and helplessness and to overcome it is necessary family support. This study aims to determine the biological and social relationship between family support and the level of anxiety in chronic kidney failure patients undergoing hemodialysis. This research was quantitative using a correlation method involving 99 patients in the hemodialysis unit at Cibinong Hospital. To collect data, this study used prepared observation sheets, and statistical analysis was carried out using the Chi Square test. This method was carefully chosen to ensure that the data obtained could be used to evaluate the relationship between biological and social levels of anxiety in hemodialysis patients. With this approach, it is hoped that this research will provide valid and useful findings in supporting efforts to improve the quality of service in the hemodialysis unit at Cibinong Hospital.